Reorganisasi karang taruna (studi kasus karang taruna “Tunas Kahuripan” Desa Ciela, Kecamatan Bayongbong, Kabupaten Garut) - Aris Tristanto; Yunilisiah Yunilisiah (Altruis: Journal of Community Services, 2022)
Karang taruna is a social organization that ideally can embody social welfare efforts in the midst of society. But in reality, most of the youth organizations’ performances in Indonesia are different than expected, one of which is the "Tunas Kahuripan" Youth Organization in Ciela Village, Bayongbong District, Garut Regency. Based on the initial assessment results, it is known that 1) karang taruna does not have a secretariat or office; 2) some residents do not know the Karang taruna management; 3) there were misunderstandings related to the main tasks of the Youth Organization. This service activity is carried out through community development through the macro social work method. Social Work Assessment Tool used by social workers Capacity Assessment (PEKA). Based on the results of the assessment, the alternative follow-up plan (RTL) chosen was the reorganization of the Youth Organizations at various levels, ranging from individuals, organizations, and systems. The author suggests at the individual level for a member of a youth organization to always maintain commitment. The authors suggest that organizations implement partnerships based on the basic strategy at the organizational level. Meanwhile, at the system level, the rules that have been set must be what they should be and the Youth Organizations should no longer belittle themselves, in other word Youth Organizations must take on a role in society.